THE INFLUENCE OF PERCEPTIONS OF BENEFITS, EASE, AND SPEED OF TRANSACTIONS ON CUSTOMER DECISIONS TO USE MOBILE BANKING FACILITIES AT INDONESIA SHARIA BANK (BSI) - Ramlah Masiga; Rafidah (IAIN Surakarta, 2023)
The research objective is to identify and analyze the influence of perceived benefits, perceived convenience and perceived transaction speed on customer decisions to use mobile banking facilities at Indonesia Sharia Bank (Case Study of students at UIN Sulthan Thaha Saifuddin Jambi). The method used in this study is a quantitative method with data collection techniques used to test the coefficient of determination of the sample in this study as many as 100 samples of UIN STS Jambi students by distributing Likert scale questionnaires. Based on the results of the t test table, it indicates that the tcount value of the Islamic lifestyle variable is 4.111 > 1.984 with a significance value of 0.000 <0.05. So it can be concluded that Ha is accepted and Ho is rejected which states that there is a significantly positive influence between the perceived benefits variable on the customer's decision variable to use Indonesia Sharia mobile banking facilities. The hedonic lifestyle is 1.566 < 1.984 with a significance value of 0.121 > 0.05. So it can be concluded that Ha is rejected and Ho is rejected which states that there is a significantly positive effect on the hedonic lifestyle variable on the buyer's decision variable. Based on the results of the t test in the table it is found that the tcount value of the hedonic lifestyle variable was 1.727 < 1.984 with a significance value of 0.087 > 0.05. So it can be concluded that Ha is rejected and Ho is rejected which states that there is a significantly positive effect on the hedonic lifestyle variable on the buyer's decision variable.